A critical examination of the VFA framework – the VFA agent and beyond. Issue 1 (2nd January 2020) - Buttigieg, Christopher P.; Sapiano, Gerd
Abstract : Malta is one of the first countries to have enacted a framework for the regulation of crypto assets. This paper examines the Maltese initiative and compares this framework with developments in other jurisdictions, particularly France, which is the only EU Member State other than Malta, to have a sui generis framework for the sector. It also examines in detail the regime applicable to VFA Agents, which have a critical role in ensuring that only operators that are fit and proper get access to Malta's financial system, thus acting as a first line of defence against the abuse of the system. The paper outlines how, through checks on an applicant for registration as a VFA Agent's governance, business model, level of competence and systems and controls, the MFSA is ensuring that registered agents can perform as the Authority's extended supervisory arm, thereby strengthening the level of monitoring in this field.